The development and the effects of storage conditions on smoked soft-boned bangus (Chanos Chanos) - Baclig, Remedios Villegas; Acevedo, Teresita P. (1972., 1972)
ABSTRACT The study hoped to develop a better method for producing smoked soft-boned bangos and an assessment of its storage qualities as related to the physico-chemical characteristics while stored at various temperatures. Preparation of smoked soft-boned bangos involved the following operations: cleaning and eviscerating the fish; soaking in brine at desired levels of salt concentration; pressure-cooking, drying and smoking at optimum times and temperatures. Objective and subjective test results indicated that the best product was obtained from soaking at 95S (degree Salometer), pressure-cooking at 15 lbs. for 1 hour and storing for about 3 weeks at 16-20C.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fish, Smoked